(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tea plays a significant role in the Indian economy as being a major export-oriented cash crop. The Northeastern Indian state of Assam is the largest producer of black tea in the world. The domestic market for tea in India has increased by 19% in between 1997 to 2010. The importance of tea lies not just in its economic value but also in its ability to provide employment to millions of workforces in rural and remote areas. Here, it should be noted that even though the tea plantations employ hundreds of thousands of workforces, this sector is at the lowest rung of organized sector with very little effective bargaining power. However, what remains unseen is the silent cry of the womenfolk engaged in the tea production. A number of studies have suggested that women who form more than half of the labour force are facing a dire situation with increasing violence and sex trafficking which has become rampart in tea growing areas. A large number of the women and children of the gardens have been pulled by promises of regular income to work as domestic workers in the metropolitan cities. Many of these migrant workers fall prey to human trafficking, whether for the sex trade or domestic work where they are made to work as virtual house slaves by domestic service agencies. Another area to be concerned of is the high maternal mortality rate in the gardens. The present paper based on extensive fieldwork and interviews throws light on the issue of falling working condition for woman workers in the tea-gardens which have made them vulnerable to kidnapping, trafficking and ultimately disappearance without any trace.